Egg traits and physiological neonatal chick parameters from broiler breeder at different ages - Luquetti, BC [UNESP]; Gonzales, E [UNESP]; Bruno, LDG [UNESP]; Furlan, Renato Luis [UNESP]; Macari, Marcos [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2004)
This investigation was carried out to study egg traits (weight, specific gravity and eggshell thickness), and neonatal chick parameters (weight, blood, cardiac and lung parameters) from breeder at different ages. After hatching, neonatal chicks, male and female, from broiler breeder at three different ages (30, 45 and 60 weeks) were sacrificed and blood (red blood cell number, hematocrit, mean cell volume, blood viscosity, and haemoglobin), cardiac (right ventricle and total ventricle weights, cardiac index) and lung (mean pulmonary pressure, fresh relative lung weight) parameters were measured. No significant differences in eggshell thickness or specific gravity were observed in eggs from the three different breeder age. The incubated eggs and neonatal chicks showed heavier absolute weights with increasing breeder age. Broiler breeder age did not affect blood parameters or cardiac index, but affected right ventricle and total ventricle absolute weights. Red blood cell number and hematocrit were higher and lung weight and lung weight:chick weight index were lower for female neonatal chicks. The findings of this study revealed that breeder age affects neonatal chick parameters such as body weight, heart and lung absolute weights, but not blood parameters.
Keywords: Broiler breeder age; Blood; cardiac; lung parameters; neonatal chicks